2018
DOI: 10.1016/j.dsr2.2017.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sea ice on the structure of phytoplankton communities in the northern Antarctic Peninsula

Abstract: The seasonal advance and retreat of sea ice around the northern Antarctic Peninsula can have a significant impact on phytoplankton, mainly due to alterations in the availability of ice-free areas, micro-nutrient inputs by meltwater and variations in water column structure. The aim of this work was to evaluate the effect of sea ice conditions on phytoplankton biomass and community composition in an area off the northern Antarctic Peninsula, a region undergoing important warming processes. In two consecutive sum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 79 publications
(91 reference statements)
4
40
0
Order By: Relevance
“…Sampling under greater influence of meltwater occurred in early summer 2013-2014 (scenario iii) and late summer 2014-2015 (scenario iv), as also observed by Mendes et al (2018) in Weddell-Scotia Confluence Zone in 2013 (sector 7). Despite the high water temperatures recorded in 2010-2011 (average 1.66 • C during late summer) only one station, Botany Point, exhibited an influence from meltwater.…”
Section: Discussion Environmental Patterns In Admiralty Bay In the Comentioning
confidence: 58%
See 3 more Smart Citations
“…Sampling under greater influence of meltwater occurred in early summer 2013-2014 (scenario iii) and late summer 2014-2015 (scenario iv), as also observed by Mendes et al (2018) in Weddell-Scotia Confluence Zone in 2013 (sector 7). Despite the high water temperatures recorded in 2010-2011 (average 1.66 • C during late summer) only one station, Botany Point, exhibited an influence from meltwater.…”
Section: Discussion Environmental Patterns In Admiralty Bay In the Comentioning
confidence: 58%
“…Lange et al (2014) observed higher salinities during the beginning than at the end of the summer, while Tenenbaum et al (2010) reported reduced salinity for neritic regions, possibly due to the presence of glaciers in the region. In this context, Mendes et al (2018) found lower values for salinity (mean 33.68) in areas near ice-covered regions and higher values (mean 34.14) in regions with little or no influence of ice cover seasonality for sector 7 (Weddel-Scotia Confluence Zone), thus correlating low salinity with water column stability. Additionally, Wasiłowska et al (2015) associated low salinities (<34) with increased water column stability and a shallow (<2 m) mixture layer in sector 1.…”
Section: Discussion Environmental Patterns In Admiralty Bay In the Comentioning
confidence: 83%
See 2 more Smart Citations
“…Consequently, remote-sensingderived CHL is now considered an essential climate variable by the Global Climate Observing System (GCOS; Bojinski et al, 2014) and a large number of studies on the response of phytoplankton community to environmental changes have been performed, particularly at a global scale (e.g., Behrenfeld et al, 2006;Rost et al, 2008;Beardall et al, 2009;Paerl and Huisman, 2009;Boyce et al, 2010;Hallegraeff, 2010;Litchman et al, 2012). Additionally, coastal studies have already shown responses of phytoplankton biomass and community structure to changes in nutrients, temperature, and salinity (SAL) (e.g., Mendes et al, 2018). However, the phytoplankton communities at a regional scale have complex variations, fluctuating from region to region and there is still much to unravel on community dynamics (e.g., Brotas et al, 2013;Brito et al, 2015).…”
Section: Introductionmentioning
confidence: 99%